Mutagenesis of Ganoderma lucidum protoplasts for high rate of biomass production and Se+4-rich isolates - LIU Shi-wang; GUO Ze-jian; KAN Yun-chao; LI Nan-yi; LI Jin (浙江大学学报. 农业与生命科学版)
Protoplasts were isolated from Ganoderma lucidum CJXN-9802. Factors including enzymes, hypha age, osmotants, and temperature were studied with respect their influence on protoplast production. Rapid growth mutants were obtained through screening from UV-light irradiated protoplasts. One of the mutants CJXN-980222 showed increase in biomass 9.4% and 14.3% increase in Se+4 content, compared with the original strain.